PENGARUH SISTEM REKRUTMEN, PELATIHAN KERJA DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN (DI PERUSAHAAN DAERAH AIR MINUM, KOTA MALANG, JAWA TIMUR) - Khoiron Sukron Sani; Hadi Sunaryo; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT This study aims to describe and analyze the influence of the recruitment system on job training, and work motivation on employee productivity in poor water companies. The company strives to get and place the right employees in accordance with their respective fields of expertise, even in the company most employees are not in accordance with the field of ability they have because most employees recruit with nepotism so that the potential for employee productivity is less than optimal. This type of research is experimental. This study uses primary data obtained from the distribution of questionnaires. This study consisted of 342 active employees with a sample of 77 employees in the Malang regional water company. Data collection through questionnaires. In this study data analysis used the SPSS 14.0 version.This research uses descriptive quantitative method which contains validity, reliability, normality, multicollinearity test, heteroscedasticity, multiple linear analysis, F test, and t test.The results of this study indicate that, (1) simultaneously the influence of the recruitment system, job training, and work motivation on employee work productivity in the Regional Water Supply Company of Malang. (2) partially the recruitment system variable does not have a significant effect on employee work productivity, further job training has a significant effect and work motivation has a significant effect on employee work productivity in the Malang water utility company. Key word: recruitment system, work training, work motivation and productivity